2014
DOI: 10.11648/j.ijnfs.20140304.13
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fiber Enriched Herbal Biscuits: A Preliminary Study on Sensory Evaluation and chemical Composition

Abstract: Abstract:The study was designed to formulate a fiber enriched herbal biscuits (Holy Basil and Moringa) that contains sufficient nutrient (protein and fiber enriched). The objectives of this research were to determine the Biochemical and organoleptic attributes of Herbal biscuit substituted with four different percentages i.e., Normal, Sample -1(1 %), Sample -2 (2 %) and Sample -3 (3%) both Tulshi and Moringa leaves. Fiber enriched herbal biscuits were developed by incorporating Tulshi (Ocimum sanctum) leaves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 10 publications
(8 reference statements)
4
29
0
Order By: Relevance
“…As previously indicated, whatever is to be added to any food as a fortificant, it must not improve the nutritional value of the food at the expense of the sensory properties.M. Oleifera seed (Ogunsina et al, 2010) or leaf (Alam et al, 2014;Dachana et al, 2010;Kar et al, 2013;Manaois et al, 2013) has also been employed in wheat biscuit or cookie fortification. Ogunsina et al (2010) reported that 20% level of M. Oleifera seed flour (MOSF) produced wheat cookies with surface cracking pattern and colour similar to the control.…”
Section: Biscuitsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously indicated, whatever is to be added to any food as a fortificant, it must not improve the nutritional value of the food at the expense of the sensory properties.M. Oleifera seed (Ogunsina et al, 2010) or leaf (Alam et al, 2014;Dachana et al, 2010;Kar et al, 2013;Manaois et al, 2013) has also been employed in wheat biscuit or cookie fortification. Ogunsina et al (2010) reported that 20% level of M. Oleifera seed flour (MOSF) produced wheat cookies with surface cracking pattern and colour similar to the control.…”
Section: Biscuitsmentioning
confidence: 99%
“…Wheat cookies fortified with 10% MOSF resulted in higher increase (45%) in protein content than those reported for wheat cookies fortified with 10% MOLP by different authors (approx. 1% increase) (Alam et al, 2014), (approx. 22% increase) (Dachana et al, 2010).…”
Section: Biscuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein, crude fiber, and ash content increased appreciably with increasing concentration of Moringa leaf powder in chocolate and halwa (Abou‐Zaid & Nadir, ). Biscuits incorporated with 5% leaf powder were reported to increase protein content by 14%, and these are known as Moringa biscuits (Alam et al, ). Bread fortified with 5% of MO leaf powder was found to have 17% and 88% increased in protein and dietary fiber content (Chinma, Abu, & Akoma, ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown the potential use of different parts of M. Oleifera in food applications such as in making soups (Babayeju et al, 2014), weaning foods (Arise et al, 2014), amala, a stiff dough made from yam and plantain flour (Karim et al, 2015(Karim et al, : 2013, herbal biscuits (Alam et al, 2014), bread (Chinma et al, 2014) and cake (Kolawole et al, 2013). The use of this nutrient rich plants in fortifying foods is getting more attention.…”
Section: Introductionmentioning
confidence: 99%